2013
DOI: 10.1111/jocn.12234
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory rate records: the repeated rate?

Abstract: Aims and objectivesTo explore the incidence and patterns of respiratory rate recording and its use as a Medical Emergency Team (MET) calling criteria, in a medical and surgical ward in a rural Australian hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 5 publications
2
33
0
Order By: Relevance
“…Misconceptions among nurses relating to blood pressure and oxygen saturation as early indicators of deterioration, and respiratory rates as the least important key indicator have been reported elsewhere (Leuvan & Mitchell, ; Mok et al., ). Previous studies have also shown that respiratory rate is often missing or not recorded in hospital documentations (Cooper, Cant, & Sparkes, ; De Meester et al., ; Ludikhuize et al., ). However, in this study, we demonstrated the effectiveness of the Web‐based program in improving the ENs’ measuring of respiratory and heart rates.…”
Section: Discussionmentioning
confidence: 99%
“…Misconceptions among nurses relating to blood pressure and oxygen saturation as early indicators of deterioration, and respiratory rates as the least important key indicator have been reported elsewhere (Leuvan & Mitchell, ; Mok et al., ). Previous studies have also shown that respiratory rate is often missing or not recorded in hospital documentations (Cooper, Cant, & Sparkes, ; De Meester et al., ; Ludikhuize et al., ). However, in this study, we demonstrated the effectiveness of the Web‐based program in improving the ENs’ measuring of respiratory and heart rates.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these known associations, breathing frequency is too commonly dismissed as an indicator of distress and recorded as an approximate value or consistently recorded as either 16 or 18. 20 Education regarding the importance of proper monitoring and reporting of values that exceed expected norms should become an integral part of orientation and continuing education for all clinicians who provide SDU care. We also found that subjects admitted from a higher-intensity monitoring unit were more likely to develop CRI, a finding that also has implications for detection of patients at highest risk.…”
Section: Discussionmentioning
confidence: 99%
“…, Cooper et al . ). A survey on nurses’ attitudes towards vital signs monitoring in detecting clinical deterioration revealed a misconception about changes in vital signs.…”
Section: Introductionmentioning
confidence: 97%
“…Being responsible for monitoring vital signs, frontline nurses play a pivotal role in detecting vital sign abnormalities. However, the incomplete measurement and documentation of vital signs particularly regarding respiratory rates, have reportedly hindered timely recognition of clinical deterioration (De Meester et al 2012, Cooper et al 2014. A survey on nurses' attitudes towards vital signs monitoring in detecting clinical deterioration revealed a misconception about changes in vital signs.…”
Section: Introductionmentioning
confidence: 99%